Vibrant Photography: Photographs, actants and political ecology. (2nd January 2016) - Peck, Julia
Abstract : Jane Bennett's thesis in Vibrant Matter argues that we need to find ways to acknowledge and engage with the agency of all factors that create ecologies and environments, including non-human actants. This essay argues that Richard Misrach and Kate Orff's project Petrochemical America signals some important strategies that are useful for developing visual political ecologies and understanding non-human actants, including the non-living. Although some of the images are typical scenes of environmental devastation, human and social links are made to foster the understanding that we are looking at an image of ecology rather than nature ravaged. In addition to the titles of images, captions and overall contextualization of the project, Kate Orff's team SCAPE produce a series of diagrams called Throughlines that situate the subject of petrochemical creation and its impact in the Mississippi River corridor. The cumulative impact of Misrach's photographic approach, combined with the effective and systematic linking of his images to other forms of relevant information by Kate Orff, produces an understanding of environment as not only inextricably linked to human activity and habitation, but which also contains differing agencies constituting a broader ecology.